2017
DOI: 10.1177/0884533616687502
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Support for Persistent Inflammation, Immunosuppression, and Catabolism Syndrome

Abstract: Despite tremendous advances in critical care, multiple-organ failure continues to be a significant problem. However, in recent years, far fewer patients with multiple-organ failure die early, but many experience ongoing immune dysregulation and are developing persistent inflammation, immunosuppression, and catabolism syndrome (PICS). Most PICS patients are discharged to nonhome destinations, fail to rehabilitate, and succumb to indolent death. From a nutrition perspective, patients with PICS experience persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 41 publications
(46 reference statements)
0
49
0
4
Order By: Relevance
“…Kommentar: Für die "chronische Phase" (persistierende Organdysfunktion ohne akute inflammatorische/infektiöse Exazerbation) existieren bislang keine großen prospektiven Studien bei kritisch kranken Patienten [114,115]. Zur weitestmöglichen Konservierung des Muskeleiweißbestands und zur Unterstützung reparativer/immunologischer Prozesse bei diesen Langzeitpatienten ist eine kontinuierliche Ernährungstherapie erforderlich, die sich am sinnvollsten am gemessenen/geschätzten Energieumsatz orientiert (isokalorische Ernährung, 100 %).…”
Section: Starker Konsens (97 %)unclassified
“…Kommentar: Für die "chronische Phase" (persistierende Organdysfunktion ohne akute inflammatorische/infektiöse Exazerbation) existieren bislang keine großen prospektiven Studien bei kritisch kranken Patienten [114,115]. Zur weitestmöglichen Konservierung des Muskeleiweißbestands und zur Unterstützung reparativer/immunologischer Prozesse bei diesen Langzeitpatienten ist eine kontinuierliche Ernährungstherapie erforderlich, die sich am sinnvollsten am gemessenen/geschätzten Energieumsatz orientiert (isokalorische Ernährung, 100 %).…”
Section: Starker Konsens (97 %)unclassified
“…In describing the persistent inflammation catabolism syndrome, Moore et al identified 3 potential pathways for patient outcome after admission to the ICU. The first pathway is rapid recovery, where the acute insult causes a systemic inflammatory response syndrome (SIRS) response, which is immediately opposed by the generation of a compensatory anti‐inflammatory response syndrome.…”
Section: Considerations Regarding the Critical Inflammatory Statementioning
confidence: 99%
“…The response to surgical stress, trauma, and sepsis includes metabolic and physiologic changes that influence the inflammatory, acute phase, hormonal, and genomic responses . This is characterized by increased catabolism and leads to impaired immune function, poor wound healing, organ failure, nosocomial infection, muscle wasting, and death . Artificial nutrition support is an essential part of managing critically ill patients and is one of the most commonly used interventions in intensive care units (ICUs).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 This is characterized by increased catabolism and leads to impaired immune function, poor wound healing, organ failure, nosocomial infection, muscle wasting, and death. 6 Artificial nutrition support is an essential part of managing critically ill patients and is one of the most commonly used interventions in intensive care units (ICUs). Clinical guidelines recommend that enteral nutrition should be the primary mode of support rather than parenteral nutrition and that it should be initiated within the first 24-48 hours following injury or admission.…”
Section: Introductionmentioning
confidence: 99%